The Role of Schools in Family-Resource Interventions to Improve Family Quality Of Life in Children with Intellectual Disabilities - Jaya, Indra; Lianty, Leliana; Taboer, Mohammad Arif; Kasirah, Irah; Rizki, Rahmat; Maulidina, Citra Ashri (VISI : Jurnal Ilmiah Pendidik dan Tenaga Kependidikan Pendidikan Non Formal, 2025)
The family plays an important role and responsibility in the development of children. School is an important part of improving the quality of individuals. School has a role in child development. The family and school are part of the microsystem environment. Unfortunately, families with children with intellectual disabilities often face different challenges than other families. Parents who have children with intellectual disabilities often feel stressed, angry, rejected, have a deep sense of guilt, and lack confidence. Family Quality of Life is a concept of how well family needs and well-being are met based on five domains: family interaction, parenting, physical well-being, emotional well-being, and disability-related services. If families do not receive support in the form of family-resourced intervention programs, this will affect the quality of families with children with special needs in a negative direction. The purpose of this research is to strengthen the role of schools to families so that families get support, information, strength, abilities, and needs of their children who experience intellectual disabilities so that a positive family quality is created because parents get the best support to create closeness and support with their children. The research method uses design and development research (D&DR). This research took place at one of the Extraordinary Schools in Jakarta. The results of the study show that schools provide full support and teachers build positive collaboration with parents so that parents have a support system from their immediate environment and can improve the quality of the family